Analysis of The Arabic Language Textbook for the Islamic Middle School for the Seventh Grade based on Multiple Intelligences - Rifa'i, Arwan (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
This research aims to analyse the 2013 curriculum Arabic language textbook based on the theory of multiple intelligences. The research uses a qualitative descriptive approach with content analysis method for the 7th grade student textbook of Islamic junior high school under the 2013 curriculum with the topic